Evaluasi Website Fakultas Ilmu Komputer Universitas Brawijaya Malang Berdasarkan Presepsi Pengguna Website Dengan Menggunakan Metode Webqual 4.0 Dan Kirkpatrick - Nur Azizah Mutmainnah; Ari Kusyanti; Yusi Tyroni Mursityo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
UB's FILKOM website is useful as a media publication and also online services media to support information requirement for students, lecturers, and academic community. As one of the websites, which are crucial for the institution the website provided must have a good quality. The lack of actual information on the FILKOM website becomes one of the problems. The quality of a website can be evaluated from the information available, the view, and the services it contains. However, not all website users are satisfied with the website, so the need to evaluate the website. Evaluation is needed to determine the feasibility of the quality of the website. The study aims to examine and determine the quality of the website FILKOM. This study uses a Webqual 4.0 analysis model that can measure the quality of information, the quality of service interaction, and the quality of the usability available on UB's FILKOM website. Having known the value of the quality of the website FILKOM, conducted Kirkpatrick evaluation to strengthen the results of research to be accepted by users and also as a reference for the website developer. The analysis used is SEM-PLS, where the analysis explains the quality of information, the quality of service interaction and the quality of usability on the FILKOM Website. The few things that are found in this study and need to be addressed include: monitoring and periodic updates regarding information contained on the website FILKOM so that users of the website to get better information and actual, then requires improvements to FILKOM Apps features because there are many features that do not work , and improvements to the menu view to make it look simpler